The Role of the Turjawali Unit in Preventing Traffic Accidents with ETLE Mobile at Magetan Police - Sanjaya, Ari (Advances in Police Science Research Journal, 2024)
In 2023, based on World Population Review, Indoensia’s population will be 278,080,459 people. The increase in population has an impact on the increasing mobility carried out by the community. To support people’s mobility using transportation. The more transportation people use, the number of traffic violations and accidents also increases. This research aims to analyze the role of the Turjawali Unit in preventing traffic accidents with ETLE Mobile at the Magetan Police Station. In writing this final assignment the author used concepts and theories which were used an analytical tools for discussion and providing problem solving for the Turjawali Unit of the Magetan Police Traffic Unit. Many implementation of action against violations by the Turjawali Unit of the Magetan Police Traffic Unit with ETLE Mobile do not comply with the rules, namely Perkakorlantas No.1 of 2022 Concering SOP for taking action against traffic violations and road transportation using electronic equipment. This discrepancy is influed by organizational resource factors so that the implementation of violation enforcement with ETLE Mobile has many problems. In the end, the author concludes that the role of the Turjawali Unit of the Magetan Police Traffic Unit in preventing traffic accidents with ETLE Mobile is not optimal. It is hoped that the problem solving provided by the author discussed in this final assignment will have a positive influence on the Turjawali Unit so that traffic accidents can decrease and the realization of a traffic security camera in the jurisdiction of the Magetan Police.